On the existence of classical solutions for differential-functional IBVP - Krzysztof A. Topolski (Abstract and Applied Analysis)
We consider the initial-boundary value problem for second order differential-functional equations of parabolic type. Functional dependence in the equation is of the Hale type. By using Leray-Schauder theorem we prove the existence of classical solutions. Our formulation and results cover a large class of parabolic problems both with a deviated argument and integro-differential equations.